Le plurilinguisme dans The Professor de Charlotte Brontë : entre fascination et neutralisation de l’altérité - Hélène Collins (Cahiers Victoriens et Edouardiens)
In Charlotte Brontë's The Professor, alterity emerges among others with foreign – mainly French – words. Their function does not only consist in producing a foreign reality effect (to borrow from Roland Barthes), that is to say in musically evoking a foreign reality, but also in constructing meaning, since their signified is not bypassed. Just like other signs, foreign words in this novel combine their signifiers, their signified, their contexts, and the effort of their readers to produce meaning. Though the text sometimes maintains ambivalence between neutralization of foreignness and harmonization with alterity, the frequent concrete occurrences of foreign signifiers makes room for alterity, testifying to a blatant fascination with alterity, notably with foreign words. Their signified is made accessible by various strategies that allow coherence between the foreign words themselves and their cotexts or translations. In a parallel to the protagonists’ wedding, The Professor harmoniously and victoriously marries French and English.